STUDI LITERATUR: PENGARUH KOMIK DIGITAL BERBASIS PJBL TERHADAP MINAT BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA SD - Putri Astuti, Nabila; Yustia Suntari; Engga Dallion EW (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Mathematics is an abstract science and is quite closely related to everyday life and its existence can fulfill students' skills outside of school. However, the reality in the field shows that students' lack of interest in learning mathematics is due to inadequate learning media in delivering mathematics. This research is aimed at finding the influence of the existence of digital comics on students' interest in learning in mathematics lessons. The method used in this research is the literature study method to examine various library sources that are relevant to the research topic. Based on the results of the literature study, it shows that there is an influence between before and after the implementation of digital comics in the classroom.